2017
DOI: 10.1007/s11192-017-2498-4
|View full text |Cite
|
Sign up to set email alerts
|

Scientific collaboration in Brazilian researches: a comparative study in the information science, mathematics and dentistry fields

Abstract: This study attempts to describe, in a comparative way, scientific collaboration and co-authoring activities and understanding of Brazilian researchers of productivity level 1 at the National Counsel of Technological and Scientific Development (CNPq). In order to do so, a questionnaire was sent to the researchers of productivity level 1 at CNPq in the Mathematics, Dentistry and Information Science fields, with questions about scientific collaboration and co-authoring activities. We analyzed the scientific produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
2
6
0
1
Order By: Relevance
“…That said, the low to absent levels of collaboration observed among many of the most productive authors identified reflects the dichotomous nature of the researchers studied: some show a markedly national orientation, while others-mainly those whose work is concentrated on performing bibliometric studies-show considerable international projection. The overall coauthorship index obtained from the set of analyzed documents (2.8) is slightly above that observed among Brazilian researchers in the area of Library and Information Science in 2010-2012 (2.2) (Hilário and Grácio, 2017), among papers published in IberoAmerican Library and Information Science journals in 2006-2014 (2.24) (Maz-Machado et al, 2015), and among the 15 core Library and Information Science journals in 2000-2011 (2.11) (Han et al, 2014). However, the coauthorship index pertaining to most of the top-producing authors is far higher, suggesting an association between productivity and degree of collaboration, albeit without excluding the potential presence of inflated coauthorship values in some cases.…”
Section: Discussion Individual Indicators For Scientific Activity Comentioning
confidence: 64%
“…That said, the low to absent levels of collaboration observed among many of the most productive authors identified reflects the dichotomous nature of the researchers studied: some show a markedly national orientation, while others-mainly those whose work is concentrated on performing bibliometric studies-show considerable international projection. The overall coauthorship index obtained from the set of analyzed documents (2.8) is slightly above that observed among Brazilian researchers in the area of Library and Information Science in 2010-2012 (2.2) (Hilário and Grácio, 2017), among papers published in IberoAmerican Library and Information Science journals in 2006-2014 (2.24) (Maz-Machado et al, 2015), and among the 15 core Library and Information Science journals in 2000-2011 (2.11) (Han et al, 2014). However, the coauthorship index pertaining to most of the top-producing authors is far higher, suggesting an association between productivity and degree of collaboration, albeit without excluding the potential presence of inflated coauthorship values in some cases.…”
Section: Discussion Individual Indicators For Scientific Activity Comentioning
confidence: 64%
“…In the present study, the average number of authors / article was 4.29. A recent study carried out with Brazilian researchers with notorious scientific production indicated that they consider four the ideal number of co-authors to enhance scientific production ( 25 ). Collaboration among authors makes research more visible, since co-authors add their scientific knowledge, enabling deeper evaluations, which, consequently, create more favorable conditions for the production of high-quality works ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The number of investigators and journals in a subarea may also influence the number of papers published yearly. A recent survey with Brazilian researchers with recognized significant scientific output indicated that they consider four as the ideal number of coauthors in order to potentiate the scientific production (12). In addition, the study showed that dental articles have an average of 5.3 authors (12).…”
Section: Introductionmentioning
confidence: 98%
“…A recent survey with Brazilian researchers with recognized significant scientific output indicated that they consider four as the ideal number of coauthors in order to potentiate the scientific production (12). In addition, the study showed that dental articles have an average of 5.3 authors (12). The connection between authors has increased over time, leading to smaller distances between researchers in the network and a larger number of coauthors (13).…”
Section: Introductionmentioning
confidence: 99%